Methods and resources in alternative scientific instrumentation for teaching sciences and engineering - Arbildo López, Aurelio (2022)
As a result of the development of low cost and high-performance scientific instruments, it has been developed some experimental set ups, measurement methods and tools (numerical and graphic) in order to obtain trustable results. Some of the assays were proof of concept that, in spite of been qualitative, have been rescued taking into account their value in the understanding of physical and chemical phenomena useful for teaching Science and Engineering. Some cases, developed by using two of the resources normally standard in personal computers such as the microphone and web cam, for sound-based tests and visible light as well as Raman spectrometry, are presented. The techniques have been developed in support of the development of Scientific Alternative Instruments (ICA in Spanish).